Effect of Duabanga grandiflora for human skin cells - Tsukiyama M. (2014)
The purpose of this investigation was to evaluate the effects of Duabanga grandiflora (Sonneratiaceae), which has been used as a traditional Thai medicine on human skin cells. The leaf extract of D. grandiflora actively affected several human skin cells such as skin whitening, anti-aging and anti-inflammation. It became evident that the extract stimulated the production of type III collagen. The crude extract was fractionated and analyzed for stimulation of type III collagen production, and finally by HPLC to isolate an active compound which was determined to be eugeniin by EI-mass, 13C NMR, 1H NMR and acidic hydrolysis. Eugeniin has strong dose dependent activity for type III collagen production, with this being the first example of stimulation activity for type III collagen production. © 2010 World Scientific Publishing Company & Institute for Advanced Research in Asian Science and Medicine.